PENDIDIKAN ISLAM SUFISTIK: Rekonstruksi Nilai-Nilai Tasawuf Dalam Pendidikan Islam Indonesia - Ahmad Mudaharahap; Nurkhodijah Nurkhodijah; Hamdani Abdi; R Mhd Kadri; Conisa Cindy (Ikhtisar: Jurnal Pengetahuan Islam, 2026)
Islamic education is currently facing a multidimensional crisis. In the face of this crisis, Islamic education has experienced a severe decline and dehumanization. As a result, the values of Islamic teachings have been stripped of their spiritual and divine essence. This study aims to reconstruct Sufi values within Islamic education (Sufi-based education) grounded in the Quran, Hadith, and the ijtihad of scholars, all rooted in divine values and spirituality. This study employs a literature review (library research) method, relying on documents as the primary data sources. The data analysis technique used in this study is content analysis, employing Sara Mills’ critical discourse framework. The results indicate that Islamic education, in the face of a multidimensional crisis, urgently requires an education grounded in Sufi values, which includes: Education must have a strong foundation rooted in spirituality based on divine values so that students may discover their innate Hanif nature. Sufi Islamic education aims to shape well-rounded individuals with praiseworthy character. To achieve this goal, Sufi Islamic education provides curriculum based on mental, spiritual, and mystical development. Sufi Islamic education also incorporates methods such as takholli, tahalli, and tajalli; these three methods require practice and habituation.